(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:The histological changes obtained from the effect of glucocorticoids on exocrine pancreas is well known but little is known about the morphometrical changes on the acinar cells and ducts which are associated with the histological findings. Objective:To reveal these morphometrical changes which are associated with the histological changes occurred on the exocrine pancreas by the use of different doses and durations of dexamethasone. Methods:Healthy female rabbits were used and divided to six groups. The first four groups regarded as the treated groups, they received different doses and different durations of dexamethasone sodium phosphate. The fifth and sixth group considered as the control group. The pancreas obtained from these animals were processed to make a paraffin blocks, the slides obtained were stained by H&E stain, and Masson?s acid Fuchin Aniline blue Trichrome stain (MT). Diameter of serous acini and intercalated ducts were measured, height of acinar cells and intercalated duct cells and counting of serous acini number in a unit area were estimated. Results:Histologically, by H&E, degenerative changes of serous acinar cells were evident which were dose and duration related. By MT stain there was decrease in collagen fibers in the interlobular spaces. Morphometrically, the diameter of serous acini, height of acinar cell and glandular density were decreased when the dose and duration of treatment were increased. Conclusion:There was increase in exhausted acinar cells as compared to metabolically active cells when the dose and duration of dexamethasone sodium phosphate treatment were increased. Key words:Exocrine pancreas, glucocorticoids and morphometery.